Histopathological Findings of Cystic Endometrial Morphology Based on Ultrasonographic Imaging in Premenopausal Women - Kinay, Tugba; Kaplan, Metin; Kayikcioglu, Fulya; Karakaya, Jale (Gynecology Obstetrics & Reproductive Medicine, 2019)
Objective: To evaluate the histopathological findings of cystic endometrial morphology based on ultrasonographic imaging in premenopausal women. Study Design: The medical records of 3607 premenopausal women that underwent ultrasonographic examination at a tertiary care center were reviewed, as were endometrial biopsy findings in 816 of the women. These 816 women were divided in 2 groups according to ultrasonographic endometrial findings: the cystic group and the non-cystic group. Clinical and histopathological findings in the 2 groups were compared. Statistical analysis was performed using independent samples t test, chi-square test, and binary logistic regression analysis. Results: Three hundred and eighty one (46.7%) of the women that underwent endometrial biopsy had cystic endometrium, whereas 435 (53.3%) had non-cystic endometrium. The most common histopathological finding in the cystic group was endometrial hyperplasia without atypia (44.6%). Cystic morphology was nearly 8-fold more common in the women with endometrial hyperplasia without atypia (95% CI: 5.43-11.67). The premalignant and malignant pathology rates in the cystic group and non-cystic group were similar (1.1% vs. 0.5% [p=0.426] and 0.8% vs. 0.5% [p=0.669], respectively). Secretory endometrium was less common in the cystic group than in the non-cystic group (5.0% vs. 37.9% [p< 0.001]) Conclusion: Cystic endometrial morphology based on ultrasonographic imaging was more common in women with endometrial hyperplasia without atypia. There wasn’t an association between cystic endometrium and other endometrial pathologies or functional endometrium. Keywords: Cystic endometrium, Endometrium, Endometrial hyperplasia, Premenopausal, Ultrasonography